A model for developing the potential of village health volunteers to prevent stroke in a risk group at Dongsansuk subdistrict health promotion hospital, Muang Ubon Rachathani district - Khanteesai, Jariya (Journal for Developing the Social and Community, 2024)
This action research aims to develop of potential for village health volunteers to prevent stroke in a risk group model at Dongsansuk subdistrict health promotion hospital, Muang Ubon Rachathani district. Research period June 2023 to July 2024. The Sample group for developing the model were public health personnel Local administrative organization, rescue workers and 12 people involved, purposive sampling. Sample group for evaluating the model were 50 village health volunteers, calculate sample size by using the G*Power program by simple random sampling. Tools used are group discussions and questionnaires. Data were analyzed using descriptive statistics, Paired Samples T Test, and content analysis. The research results found that: The model for developing the potential of village health volunteers to prevent stroke in high-risk groups Dong Saen Suk sub-district health promoting hospital consists of 7 activities: 1) assessing needs, 2) developing a curriculum to develop the potential of village health volunteers, 3) training to develop the potential Village health volunteers in caring for patients at risk of stroke 4) development of health education media, warning communication cards 5) demonstration/practice 6) developing communication systems/channels 7) monitoring and evaluating results. When the model was used, it was found that the sample group Village health volunteers have knowledge about risk factors and warning signs of stroke and skills in caring for groups at risk for stroke increased more than before the development of the model Can be used with groups of village health volunteers and extend the results to the general public.